Transfusion medicine hackathon: Nurturing the innovative ideas to revolutionize voluntary blood donation - Shamee Shastry; Gajendra Nath Gupta; Sadhana Mangwana; Nabajyoti Choudhury; Arun Shanbhag; Suchet Sachdev (Asian Journal of Transfusion Science)
BACKGROUND AND OBJECTIVE: Blood transfusion is an essential component of health care. However, several issues can hamper the promotion and sustainability of voluntary blood donation programs. This article is about a hackathon in the field of transfusion medicine that was designed to stimulate original ideas to promote voluntary blood donation. MATERIALS AND METHODS: The transfusion medicine hackathon was conducted as a joint project of an educational institute, the Asian Association of Transfusion Medicine, and the Innovation Center. It was conducted in eight main phases, which included planning and preparation, choosing the problem statement, participant recruitment and registration, launch, and mentoring as the first steps. Participants presented their ideas in the ideation phase, and the top five teams were selected for the prototyping phase. Selection was based on innovation/originality (10 points), feasibility (10 points), and social impact (5 points). In the prototype phase, two teams were selected as winners and were awarded by the organizers. RESULTS: A total of 36 multidisciplinary teams representing various parts of India pitched innovative ideas. The majority have proposed new strategies for the retention of blood donors to maintain the donor pool and teams came up with novel ideas aimed at enhancing the overall blood donation experience. One of the winning teams completed the project and launched the product. CONCLUSION: Health-care hackathons promote interdisciplinary education and innovation. This is a first-of-its-kind effort from the field of transfusion medicine to explore a hackathon platform to promote voluntary blood donation.